Editorial Note - Cosmas, Munga (Multidisciplinary Journal of Technical University of Mombasa, 2025)
Editorial NoteWe would like to thank all our authors and co-authors who contributed to the  successful release  of this Issue 2 of Volume 4, 2025 of MJTUM. There are a total of 7 publications from different authors and co-authors, out of these 5 are research articles and 2 are review articles. These published articles cover a diverse array of fields ranging from Chemistry, Marine and Fisheries Sciences, Architecture and Built Environment, Biotechnology, to Mechanical and Automotive Engineering. The content of all the articles is as a result of dedicated research works from the authors and co-authors. MJTUM is hereby providing a platform to share the contents of these research and review works in contributing to knowledge dissemination to the scientific community and to all students in their quest to advance knowledge in their respective fields. MJTUM will continue to provide a platform for dissemination of high quality scholarly articles. It is my sincere hope that you will enjoy reading the wide scope of these published articles in this current issue as we prepare you for the release of Volume 5 of 2026. Prof. Cosmas Nzaka MungaChief Editor, MJTUM